2020
DOI: 10.1108/rbf-01-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Overconfidence and financial decision-making: a meta-analysis

Abstract: PurposeThis meta-analysis reviews and summarizes the results of 34 studies to investigate the relationship between overconfidence and financial decision-making.Design/methodology/approachA correlation meta-analysis was conducted with three moderators of the relationship between overconfidence and financial decision-making examined: the type of overconfidence construct, the type of overconfidence measuring method and the type of financial decision-making.FindingsIt was found that the effect of overconfidence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 125 publications
2
18
1
Order By: Relevance
“…After the influential work of Modigliani and Miller (1958), the BF approach has revealed useful results in the process of solving decision makers' behaviors and thoughts. Grezo (2020) in this regard found the strong indirect effect of OVERCB than the direct effect.…”
Section: Manager's Capital Structure Decisions (Csds)mentioning
confidence: 73%
“…After the influential work of Modigliani and Miller (1958), the BF approach has revealed useful results in the process of solving decision makers' behaviors and thoughts. Grezo (2020) in this regard found the strong indirect effect of OVERCB than the direct effect.…”
Section: Manager's Capital Structure Decisions (Csds)mentioning
confidence: 73%
“…In order to synthetize these multiple definitions, the psychological literature conceptualized overconfidence as an umbrella composed by three different conditions, namely overprecision, overplacement and overestimation (Grežo, 2021). In detail, overprecision is related to the “systematic underestimation of the variance of a relevant measure affecting performance (demand, costs, etc.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…However, the results of the study found that the impact of negative media reports was actually minimal. However, Greo (2021) and Mundi and Kaur (2022) believe that the media does not have a unilateral impact on investment efficiency, but has both positive and negative impacts. Media reports can attract managers’ attention, improve investment prudence, and make more rational investments.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Huang et al (2022) expanded the scope of enterprise managers from a single manager to the entire company management, and found that the two are still positively correlated. Greo (2021) and Mundi and Kaur (2022) pointed out that managers with overconfidence will be keen on enterprise expansion strategies and realize enterprise expansion by increasing investment in mergers and acquisitions, but the result will increase the possibility of companies falling into financial crisis. Blair et al (2022) refined the scope of investment and defined it as the investment in fixed assets by enterprises.…”
Section: Research Hypothesismentioning
confidence: 99%